Conservative Accounting and Linear Information Valuation Models* - Choi, Young‐Soo; O'Hanlon, John F.; Pope, Peter F. (Contemporary Accounting Research, 2006)
Prior research using the residual income valuation model and linear information models has generally found that estimates of firm value are negatively biased. We argue that this could result from the way in which accounting conservatism effects are reflected in such models. We build on the conservative accounting model of Feltham and Ohlson 1995 and the Dechow, Hutton, and Sloan 1999 (DHS) methodology to propose a valuation model that includes a conservatism‐correction term, based on the properties of past realizations of residual income and “other information”. “Other information” is measured using analyst‐forecast‐based predictions of residual income. We use data comparable to the DHS sample to compare the bias and inaccuracy of value estimates from our model and from models similar to those used by DHS and Myers 1999. Valuation biases are substantially less negative for our model, but valuation inaccuracy is not markedly reduced.